Recovery following Thyroxine Treatment Withdrawal, but Not Propylthiouracil, Averts In Vivo and Ex Vivo Thyroxine-Provoked Cardiac Complications in Adult FVB/N Mice. (16th July 2017) - Saad, Nancy S.; Repas, Steven J.; Floyd, Kyle; Janssen, Paul M. L.; Elnakish, Mohammad T.
Abstract : Persistent cardiovascular pathology has been described in hyperthyroid patients even with effective antithyroid treatment. Here, we studied the effect of a well-known antithyroid drug, propylthiouracil (PTU; 20 mg/kg/day), on thyroxine (T4; 500 µ g/kg/day)-induced increase in blood pressure (BP), cardiac hypertrophy, and altered responses of the contractile myocardium both in vivo and ex vivo after 2 weeks of treatment. Furthermore, the potential recovery through 2 weeks of T4 treatment discontinuation was also investigated. PTU and T4 recovery partially reduced the T4-prompted increase in BP. Alternatively, PTU significantly improved the in vivo left ventricular (LV) function with no considerable effects on cardiac hypertrophy or ex vivo right ventricular (RV) contractile alterations subsequent to T4 treatment. Conversely, T4 recovery considerably enhanced the T4-provoked cardiac changes both in vivo and ex vivo. Altogether, our data is in agreement with the proposal that hyperthyroidism-induced cardiovascular pathology could persevere even with antithyroid treatments, such as PTU. However, this cannot be generalized and further investigation with different antithyroid treatments should be executed. Moreover, we reveal that recovery following experimental hyperthyroidism could potentially ameliorate cardiac function and decrease the risk for additional cardiac complications, yet, this appears to be model-dependent and should be cautiously construed.